Pengaruh Kepuasan Kerja Dan Lingkungan Kerja Terhadap Turnover Intention Pada Karyawan PT Jaya Teknik Artha Makmur Tangerang - Fina Febiyana; Irwin Ananta Vidada; Seno Sudarmono Hadi (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Turnover retention refers to the tendency or desire of an employee to leave the current job or organization. This may reflect the employee's thoughts, feelings, or plans regarding leaving the position in the near future. This study aims to see how the effect of job satisfaction and work environment on turnover intention of PT. Jaya Teknik Artha Makmur. This study consists of three variables, namely job satisfaction, work environment and turnover intention. The research method used is descriptive quantitative with primary data collection techniques with data collection in the form of questionnaires distributed to 41 employees as respondents. The data analysis technique used in this research is descriptive, data instrument test which includes validity and reliability tests, classic assumption test which includes normality, multicollinearity, heteroscedasticity, and autocorrelation tests, multiple linear regression tests includes t test, F test and test of the coefficient of determination. The results of this study indicate that the independent variable i.e. work environment has a negative effect on turnover intention with a significance value of 0.031 <0.05 and job satisfaction has a negative effect on turnover intention with a significant value of 0.039 <0.05 and the adjusted R squared value obtained is a 36.7%, which means that the influence between work environment and job satisfaction on turnover intention is in the low category.